(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present study is aimed to study the anti-inflammatory and anti-hemorrhoidal effect of Martynia annua and Tephrosia purpurea extracts in rats. Aerial parts of Tephrosia purpurea and leaves of Martynia annua were selected for extraction with petroleum ether and ethanol. Flavonoid-rich extracts were tested for anti-inflammatory and anti-hemorrhoidal activities (200 and 300 mg/kg bwt.). The anti-inflammatory effect was investigated on Carrageenan and histamine-induced paw edema models by measuring percent inhibition of paw edema at different time intervals. The anti-hemorrhoidal activity was studied by using croton oil-induced hemorrhoid on rats. Effect was assessed by measuring pro-inflammatory mediators in blood, Severity score and Recto Anal Co-efficient and antioxidants level in rectoanal tissues of rats. Results of the study indicate that flavonoid-rich extract of Tephrosia purpurea and Martynia annua significantly inhibited edema in a dose-dependent manner with the treatment of 200 and 300 mg/kg b.wt p.o. in both methods. Both extracts are significantly able to restore pro-inflammatory mediators (TNF-α, IL-6 and PGE2) near normal level. Both, flavonoid-rich extracts treated group also maintained Severity score and rectoanal coefficient (0.268 ± 0.08 and 0.405 ± 0.11) near to the normal control group of animals. MDA level was found statistically significant (p < 0.001) decreased after five days of treatment. The tissue antioxidant level is very close to the normal level after treatment with both flavonoid-rich extracts. The present study concluded that the anti-inflammatory and anti-hemorrhoidal effect of flavonoid-rich extracts of Martynia annua and Tephrosia purpurea could be due to the presence of major flavonoid components, namely quercetin and luteolin in both plants.